Technology addiction and phubbing behaviour in the generation Z of Pakistan - Bajwa, Ruqia Safdar; Abdullah, Haslinda; Wan Jaafar, Wan Munira; Abu Samah, Asnarulkhadi (Medical Forum, 2021)
Objective: To check the impact of internet addiction and smartphone addiction on phubbing behavior in Generation Z.. Study Design: Cross-sectional survey research study. Place and Duration of Study: This study was conducted online at University Putra Malaysia on the students of two public sector universities in Pakistan (Bahauddin Zakariya University, Multan and Islamia University, Bahawalpur) from June 2020 till August 2020. Materials and Methods: Students from two public universities in Pakistan's Southern Punjab province were sampled with a multistage cluster sampling technique. Internet addiction, smartphone addiction, and phubbing behavior were measured with reliable and valid instruments, and IBM-SPSS-23 was used to analyze the data of 794 students. A Chi-square test of independence and linear regression were used to check statistical significance. Results: Results from the Chi-square test of independence in the relation between technology use patterns and gender (47% males and 53% females) were significant (p< .001). The regression results show that model was fit F (2,791) =35.786, p<.001, and internet and smartphone addiction predicted phubbing behavior significantly (b= .072; .131, p< .001). Conclusion: Individuals differ significantly in technology use patterns according to gender. Internet addiction and smartphone addiction play a significant role in eliciting phubbing behavior.